Enhancing visible light photocatalytic activity of direct Z-scheme SnS2/Ag3PO4 heterojunction photocatalysts. (September 2016) - Luo, Jin; Zhou, Xiaosong; Ma, Lin; Xu, Limei; Xu, Xuyao; Du, Zhihua; Zhang, Jinquan
Graphical abstract: Highlights: Novel direct Z-scheme SnS2 /Ag3 PO4 heterojunction photocatalysts are synthesized. SnS2 /Ag3 PO4 exhibits much higher photocatalytic activity than pure SnS2 and Ag3 PO4 . A possible photocatalytic mechanism was discussed in detail. Abstract: Novel direct Z-scheme SnS2 /Ag3 PO4 heterojunction photocatalysts were successfully fabricated with SnS2 nanoplates hybridized by Ag3 PO4 nanoparticals via a facile hydrothermal and precipitation method and applied for the photocatalytic degradation of methyl orange in aqueous solution under visible light irradiation (λ > 420 nm). It was found that the photocatalytic performance of the SnS2 (2.0 wt%)/Ag3 PO4 heterojunction photocatalyst with 2.0 wt% SnS2 content was much higher than that of individual SnS2 and Ag3 PO4 . The enhanced photocatalytic activity could be ascribed to the efficient separation of photogenerated electrons and holes through the formation of direct Z-scheme system composed of SnS2 and Ag3 PO4 . Furthermore, the recycling experiments revealed that the photocorrosion behavior of Ag3 PO4 was strongly inhibited by SnS2, it may be due to the photogenerated electrons of Ag3 PO4 would be quickly combined with the photogenerated holes of SnS2 . This work will be useful for the design of other direct Z-scheme visible-light-driven photocatalytic systems for application in energy conversion and environmental remediation.